2013
DOI: 10.3109/01902148.2013.802828
|View full text |Cite
|
Sign up to set email alerts
|

C-Kit/c-Kit ligand interaction of bone marrow endothelial progenitor cells is influenced in a cigarette smoke extract-induced emphysema model

Abstract: The interaction between c-Kit and sKitL in bone marrow EPCs, a critical step in endothelial repair, is negatively affected in a CSE-induced emphysema model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…However, the inhibition of COX-2 expression by (26)(27)(28)(29)(30)(31). Tobacco consumption plays a critical role in the pathogenesis of pulmonary vascular abnormalities in COPD, of which the pulmonary vascular endothelial dysfunction is characteristically exhibited (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition of COX-2 expression by (26)(27)(28)(29)(30)(31). Tobacco consumption plays a critical role in the pathogenesis of pulmonary vascular abnormalities in COPD, of which the pulmonary vascular endothelial dysfunction is characteristically exhibited (32).…”
Section: Discussionmentioning
confidence: 99%
“…30 C-Kit/c-Kit ligand interaction of bone marrow-derived EPCs was influenced in a CSE-induced emphysema model. 33 EPCs with normal self-renew, proliferatory capacity, differentiative potential are essential for their own trans-endothelia shift, homing to injured location, repairment, and regeneration of various tissues and organs. Oxidative stress could lead to premature EPCs ''aging''.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most momentous risk factor of COPD, cigarette smoke could initiate apoptosis in macrophages, fibroblasts, vascular endothelial cells and epithelial cells. 22,23 Multiple evidence indicates that direct exposure to CSE affects miRNA expression in various lung diseases, including COPD. 24 A recent study reported that miR-34a was correlated with CSE-stimulated lung endothelial cell apoptosis in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition to the key genes related to COPD pathogenesis, non-coding RNAs containing microRNAs (miRNAs) have been shown to be concerned with COPD. 10,11 miRNAs, with [19][20][21][22][23][24][25] nucleotides, are a series of small endogenous nucleotide RNAs that participate in various biological processes by negatively modulate genes expression under post-transcriptional level. 12,13 The dysregulation of miRNAs are involved in multifarious diseases including COPD, which are often utilized as biomarkers for exposure to environmental factors.…”
Section: Introductionmentioning
confidence: 99%